Soybean processing wastes and their potential in the generation of high value added products - Canaan, Josiane Márcia Maria [UNESP]; Brasil, Giovana Sant'Ana Pegorin [UNESP]; de Barros, Natan Roberto [UNESP]; Mussagy, Cassamo Ussemane [UNESP]; Guerra, Nayrim Brizuela [UNESP]; Herculano, Rondinelli Donizetti [UNESP] (Elsevier, 2022)
Soybean and its derivatives are rich sources of nutrients and bioactive compounds with antioxidant properties, however, the wastes with high nutritional value are discarded by the industry. This study aimed to evaluate centesimal composition, microbial safety and antioxidant activity of soybean processing wastes (okara and okara flour) and soymilk. High fiber, carbohydrate, energy and lipids contents were found. Antioxidant activity by spectrophotometric and Electron Paramagnetic Resonance assays showed values for soybean (72.4% and 83.5%), okara (9.6% and 7.7%), okara flour (30.7% and 11.5%) and soymilk (28.4% and 36.5%). The total phenolic content was an average of 3.33 mg of gallic acid equivalent.g−1. Infrared spectra revealed no significant changes in the absorption bands, guaranteeing non-alteration in the compounds composition after processing. Microbiological assays indicated that soybean derivatives are safe for consumption. These results reinforce that these wastes contain bioactive compounds of interest with great potential to generate high value added products.
Keywords: Antioxidant activity; Centesimal composition; Electron paramagnetic resonance; Phenolic content; Soybean; Waste